A comprehensive chloroplast DNA-based phylogeny of the genus Potentilla (Rosaceae): implications for its geographic origin, phylogeography and generic circumscription - Dobeš, Christoph; Paule, Juraj (Molecular phylogenetics and evolution, 2010)
A reconstruction of phylogenetic relationships based on three chloroplast DNA markers comprising 98 species of the genus Potentilla and 15 additional genera from the tribe Potentilleae (Rosaceae) is presented. The phylogeny supported the current generic concept of the subtribe Fragariinae and resolved major lineages within the subtribe Potentillinae. Resolved lineages corresponded to the combined genera Argentina, Piletophyllum, and Tylosperma, an European and Asian group of species approximately equivalent to the Trichocarpae Herbaceae sensu Th. Wolf, the series Tormentillae Th. Wolf, a North American clade comprising the genera Horkelia, Horkeliella, and Ivesia, the species Potentilla fragarioides and P. freyniana, and to a taxonomically highly diverse but molecularly little diverged core group of Potentilla, respectively. Age estimates of phylogenetic splits resolved in the Potentilleae using Bayesian inference, suggested a diversification of the tribe in the Eocene and radiation of two major evolutionary lineages corresponding to the Fragariinae and Potentillinae at approximately comparable times. Ancestral area reconstructions based on the recent distribution ranges of species and collection sites of cpDNA haplotypes suggested an Asian origin for Potentilla s.str., and explained the arrival of this still informal taxon in Europe and particularly North America by multiple dispersal events. In combining the phylogenetic and geographic data with molecularly inferred time estimates and taxonomy, strongly contrasting evolutionary patterns were identified. These evolutionary patterns included rapid speciation on a continental and worldwide scale accompanied by multiple intercontinental dispersals opposed to largely diverged lineages of limited taxonomic diversity and vicariant geographic distribution. The molecular-based phylogeographic hypothesis finally is discussed on the background of the fossil record of Potentilla.
Gesehen am 06.02.2023